2018
DOI: 10.3389/fimmu.2018.00786
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Regulatory T Cells to Treat Patients With Systemic Lupus Erythematosus

Abstract: Regulatory T cells (Tregs) are central in integration and maintenance of immune homeostasis. Since breakdown of self-tolerance is a major culprit in the pathogenesis of systemic lupus erythematosus (SLE), restoration of the immune tolerance through the manipulation of Tregs can be exploited to treat patients with SLE. New information has revealed that Tregs besides their role in suppressing the immune response are important in tissue protection and regeneration. Expansion of Tregs with low-dose IL-2 represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 106 publications
(113 reference statements)
1
49
0
4
Order By: Relevance
“…A number of factors contribute to the development of LN, including genetic mutation, hormonal imbalance, environmental challenging and presence of drugs . Although the precise pathogenesis of LN is not completely understood, numerous clinical and animal studies have demonstrated that B cells, proinflammatory Th17 cells and regulatory T cells (Tregs) play a critical role in the pathogenesis of LN …”
Section: Introductionmentioning
confidence: 99%
“…A number of factors contribute to the development of LN, including genetic mutation, hormonal imbalance, environmental challenging and presence of drugs . Although the precise pathogenesis of LN is not completely understood, numerous clinical and animal studies have demonstrated that B cells, proinflammatory Th17 cells and regulatory T cells (Tregs) play a critical role in the pathogenesis of LN …”
Section: Introductionmentioning
confidence: 99%
“…Применение ИЛ2 в лечебных целях осложняется очень коротким периодом его полувыведения (около 5-7 мин), в связи с чем разрабатываются новые формы ИЛ2: например, ИЛ2, модифицированный с полиэтиленгликолем, или человеческие ИЛ2-анти-ИЛ2-иммунные комплексы, которые обладают более длительным периодом полувыведения и способствуют продолжительной пролиферации и активации Т-рег-клеток. Кроме того, использование наночастиц ИЛ2, меченных антителами, распознающими специфические ткани, позволяет добиться более адресной доставки препарата [48].…”
Section: т-рег-клетки в терапии аутоиммунных заболеванийunclassified
“…Ранее сообщалось об эффективности использования данного метода на мышиных моделях СКВ [49]. Недавно инициировано исследование введений аутологичных Т-рег-клеток у больных СКВ (NCT02428309) [48].…”
Section: т-рег-клетки в терапии аутоиммунных заболеванийunclassified
“…The etiology of pSS is currently unclear, but previous studies have suggested that the human immune system could produce auto‐antibodies that target and damage exocrine glands, which play a central role in the development of pSS 1,2 . Sustained perturbations of the immune system are harmful to the host and eventually result in disease conditions such as rheumatoid arthritis (RA), 3,4 systemic lupus erythematosus (SLE) 5,6 and cancer 7 …”
Section: Introductionmentioning
confidence: 99%